Antiplasmodial and Cytotoxic Activity of Raw Plant Extracts as Reported by Knowledgeable Indigenous People of the Amazon Region (Vaupés Medio in Colombia) - Pabón, Adriana; Ramirez, Otoniel; Ríos, Alexandra; López, Ena; de las Salas, Briegel; Cardona, Felipe; Blair, Silvia (Planta Medica, 2016)
The in vitro antiplasmodial activity of 122 raw extracts prepared in ethanol and water from 35 medicinal plants reported by the Cubeo indigenous village of the Amazon region (Vaupés Medio in Colombia) was evaluated for efficacy against 3D7 (sensitive to chloroquine) and FCR-3 (resistant to chloroquine) Plasmodium falciparum strains. Five percent of these extracts presented a significant antiplasmodial activity (< 5 µg/mL) and 83 % of them were not cytotoxic. These findings highlight the importance of investigating traditional medicinal plants implemented by these ancestral communities of the Amazon region as well as their potential to become a source of new drugs against malaria.
Keywords: antimalarial plants; indigenous communities; Amazon region; Plasmodium falciparum